Cognitive changes after epilepsy surgery in the posterior cortex. Issue 4 (16th March 2004) - Luerding, R; Boesebeck, F; Ebner, A
Abstract : Objective: The relationship between the posterior cortex and cognitive functions is still a relatively open field. There are no studies on populations in which functions of posterior structures were examined by a standardised neuropsychological examination before and after posterior resections. Changes in cognitive performance are regularly observed after epilepsy surgery in the temporal lobe. However, information about neuropsychological impairments after resections in the posterior cortex is poor, owing to the relatively low proportion of cortical resections in this area. Methods: We retrospectively studied changes in cognition in the neuropsychological data of 28 patients prior to and 6 months after posterior cortical resections. Results: Cognition significantly showed differences in performance intelligence quotient compared with verbal intelligence quotient. Post-operative verbal intelligence consistently increased, whereas performance intelligence decreased. There was no effect regarding the lesion side, continuation of seizures, or reduction of visual field after surgery. Epilepsy surgery in this area did not lead to significant differences in general intelligence after surgery. Conclusion: Functions of posterior areas could be described by standardised neuropsychological measures. Posterior regions contribute to explicit attentional and visuoconstructional abilities. Epilepsy surgery in the posterior cortex bears no risk for substantial decline in general cognition although some discrete impairment in performance intelligence may occur.